As discussões de gênero na formação de docentes de ciências da natureza - Macedo, Jéssica Carolina Paschoal de (Universidade Federal de São Carlos, 2020)
This research aims to analyze the formative potential of the Curricular Activity of Integration Teaching, Research and Extension (ACIEPE) proposed, aiming to identify the implications arising from the insertion of gender issues as a socio-scientific issue in the training of future / science teachers. In this way, the present work was developed with students of the courses of Degree in Chemistry, Physics and Biological Sciences, Bachelor in Biotechnology and Master in Education for Science, from UFSCar - Center for Agricultural Sciences. It is a participatory research, since the interaction based on the strengthening of communicative and horizontal relations between the researchers and the participants occurred during all stages of the research, highlighting the moments of theoretical discussion and action proposals oriented to social transformation. In this sense, the inferences pointed out result from the data categorization process, based on the content analysis methodology proposed by Bardin, the categories being discussed, the time available for the activities proposed at ACIEPE, the absence of the participation of the external community, recognition of gender theories such as scientific knowledge, consolidation of communicative spaces for training and transformation through research. That said, through the delimited categories we conclude that, based on reasoned discussions about the potentialities, limitations and intentionalities of scientific and technological studies as a mechanism to face social inequalities, the critical, engaged and active formation in the search for social justice occurred. Thus, we hope with this work to add new knowledge to gender discussions in the formation of future science teachers.
Gender discussions in the training of nature science teachers
Keywords: Formação docente; Ensino de ciências; Questões sociocientíficas; Discussões de gênero; Formação docente para justiça social; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM